2019
DOI: 10.1029/2019jb017539
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Megathrust Earthquakes Across Scales: One‐way Coupling From Geodynamics and Seismic Cycles to Dynamic Rupture

Abstract: Taking the full complexity of subduction zones into account is important for realistic modeling and hazard assessment of subduction zone seismicity and associated tsunamis. Studying seismicity requires numerical methods that span a large range of spatial and temporal scales. We present the first coupled framework that resolves subduction dynamics over millions of years and earthquake dynamics down to fractions of a second. Using a two-dimensional geodynamic seismic cycle (SC) model, we model 4 million years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 121 publications
(198 reference statements)
1
58
0
Order By: Relevance
“…Due to the major numerical challenge of resolving both millions of years and subsecond time scales, events have an unrealistically long duration, as a large 5 year time step limits computations. This does not allow us to resolve earthquake nucleation and dynamics, which could affect the recurrence interval and slip distribution (van Zelst et al., 2019). However, the main findings of this paper are determined by long‐term characteristics that are not affected by the limited time resolution of our approach.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the major numerical challenge of resolving both millions of years and subsecond time scales, events have an unrealistically long duration, as a large 5 year time step limits computations. This does not allow us to resolve earthquake nucleation and dynamics, which could affect the recurrence interval and slip distribution (van Zelst et al., 2019). However, the main findings of this paper are determined by long‐term characteristics that are not affected by the limited time resolution of our approach.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical conditions that lead to a wide range of earthquake sizes along a plate boundary and the role of fault geometry in earthquake segmentation remain poorly understood. Fault bends are relevant to earthquake initiation and termination processes (King & Nábėlek, ; King, ), and studies of dynamic earthquake ruptures with geometric complexities have shown significant off‐fault deformation (Aochi et al, ; Duan & Day, ; Kase & Day, ; Preuss et al, ; van Zelst et al, ; Zhang et al, ). Previous work on the dynamics of ruptures at fault bends is often limited to single‐cycle ruptures (Aochi et al, ; Lozos et al, ; O'Reilly et al, ; Poliakov et al, ; Rousseau & Rosakis, ), but a multi‐cycle approach is required to discuss rupture dynamics and seismic supercycles (e.g., Dal Zilio et al, ; Herrendörfer et al, ; Ong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…All faults are exposed to the same local stress regime while experiencing varying ratios of shear and normal loading, depending on their orientation towards this loading. Even a small change in fault geometry (e.g., in strike, dip, size, and the angle between fault planes) strongly affects the dynamic rupture result (e.g., Yamashita and Umeda, 1994;Aochi et al, 2005;Bhat et al, 2007;Ulrich et al, 2019a;van Zelst et al, 2019), as illustrated when comparing Model 1F and Model 2F. We point out that trade-offs between the inferred stress state and fault geometry can be readily explored if new observations become available.…”
Section: Model 2f Validation By Regional Waveform Modelingmentioning
confidence: 84%